Treatment for acute anterior cruciate ligament tear: five year outcome of randomised trial - Frobell, Richard B.; Roos, Harald P.; Roos, Ewa M.; Roemer, Frank; Ranstam, Jonas; Lohmander, L. Stefan (British Journal of Sports Medicine, 2015)
In young active adults with an acute anterior cruciate ligament (ACL) rupture, do patient reported or radiographic outcomes after five years differ between those treated with rehabilitation plus early ACL reconstruction and those treated with rehabilitation and optional delayed ACL reconstruction?At five years, patients assigned to rehabilitation plus early ACL reconstruction did not differ significantly in patient reported or radiographic outcomes from those assigned to initial rehabilitation with the option of having a later reconstruction if needed.The relative efficacy of surgical reconstruction and rehabilitation for short and long term outcomes of ACL rupture is debated. Clinicians and young active adult patients should consider rehabilitation as a primary treatment option following an acute ACL tear.
EVALuna2:14540